Alterations in the Secretome of Clinically Relevant Preparations of Adipose-Derived Mesenchymal Stem Cells Cocultured with Hyaluronan - Peter Succar; Edmond J. Breen; Donald Kuah; Benjamin R. Herbert (Stem Cells International)
Osteoarthritis (OA) can be a debilitating degenerative disease and is the most common form of arthritic disease. There is a general consensus that current nonsurgical therapies are insufficient for younger OA sufferers who are not candidates for knee arthroplasties. Adipose-derived mesenchymal stem cells (MSCs) therapy for the treatment of OA can slow disease progression and lead to neocartilage formation. The mechanism of action is secretion driven. Current clinical preparations from adipose tissue for the treatment of OA include autologous stromal vascular fraction (SVF), SVF plus mature adipocytes, and culture-purified MSCs. Herein we have combined these human adipose-derived preparations with Hyaluronan (Hylan G-F 20: Synvisc) in vitro and measured alterations in cytokine profile. SVF plus mature adipocytes showed the greatest decreased in the proinflammatory cytokines IL-1β, IFN-γ, and VEGF. MCP-1 and MIP-1α decreased substantially in the SVF preparations but not the purified MSCs. The purified MSC preparation was the only one to show increase in MIF. Overall the SVF plus mature adipocytes preparation may be most suited of all the preparations for combination with HA for the treatment of OA, based on the alterations of heavily implicated cytokines in OA disease progression. This will require further validation using in vivo models.